Familiarity with the Open Access Movement among Faculty Members of Golestan University of Medical Sciences, Iran - Masoud Mohammadi; Masoumeh Mirkarimi; Safiyeh Tahmasebi Limooni (Golestan University Of Medical Sciences, 2018)
Background and objectives: Free (open) access to scientific information has emerged as a new paradigm to resolve existing problems and to improve the scientific communication process. This study was conducted to evaluate the level of familiarity with the open access movement among faculty members of Golestan University of Medical Sciences, Iran. methods: A pre-made questionnaire was utilized in this analytical survey. Cronbach's α of 0.75 verified the reliability of the questionnaire. The study included 157 faculty members employed via non-probability randomized sampling and the Cochran's sample size formula. Descriptive statistics, Kolmogorov-Smirnov test, Tukey's test and Pearson correlation were used to analyze the data. Results: Faculty members had little acquaintance with the open access to scientific information. The greatest level of familiarity was with ''open access journals'' (mean score: 2.42), while the lowest level of familiarity was with ''the open access movement'' (mean score: 3.07). Conclusions: The faculty members of the Golestan University of Medical Sciences have relatively moderate level of familiarity (compared to other universities in the country) with the open access movement, but it is still far from ideal. Given the importance of free access to scientific information and its positive impact on the visibility and credibility of scientific products, it is essential to plan and take action to raise awareness and promote implementation of this movement among faculty members.